Responsible management and taoism. Volume 1, - Zu, Liangrong (Emerald Publishing Limited, 2023)
In this thought-provoking Volume One of the series, Managing Responsibly for Sustainable Business Development in the VUCA World, We embark on a transformative journey towards sustainable and excellent management practices. As the world grapples with the complexities and uncertainties of the VUCA (volatile, uncertain, complex, and ambiguous) era, it has become imperative to explore new approaches that align with responsible management and Taoist principles. This volume serves as a comprehensive introduction to the 3C Model of Taoism - compassion, conservation, and compliance, which forms the foundation for sustainability and excellence. Through a deep exploration of the relationships among business, management, leadership, sustainability, and excellence, readers gain valuable insights into how these aspects intertwine to shape responsible management in today's dynamic landscape. Furthermore, Volume One explores the adaptive challenges and wicked problems that organizations face in the VUCA world. It provides guidance on shifting the management paradigm to adapt to these challenges and effectively address wicked problems within complex organizations. When adopting the 3C Model of Taoism, managers and leaders will discover how to manage people with compassion, embracing social responsibility; manage organizations with conservation, fostering ecological sustainability; and manage businesses with compliance, upholding strong business ethics. Volume One is an indispensable resource for managers, leaders, and scholars seeking innovative solutions and a deeper understanding of responsible management practices. Drawing from the profound wisdom of Taoism, this volume offers practical insights and strategies to navigate the complexities of the VUCA world while upholding values of compassion, conservation, and compliance. Volume One is one of a two-volume series. Volume Two, Transforming Management Education for Sustainable Development Goals (SDGs), explores the crucial role of transforming management education to meet the challenges and goals of sustainable development. Together, these volumes provide a comprehensive and enlightening exploration of responsible management, Taoism, and their impact on overcoming challenges in the VUCA era.